The Perceived Ostomy Educational Needs of Pediatric Patients With Inflammatory Bowel Disease and Their Caregivers. Issue 6 (June 2020) - David, Jennie G.; Moreno, Steffany; Daniel, Rhea; Pall, Harpreet
Abstract : ABSTRACT: Inflammatory bowel disease (IBD) is a chronic disease causing inflammation of the gastrointestinal tract. Some patients require ostomy surgery to optimize their health. This study assessed perceived medical and psychosocial educational needs related to ostomy surgery in pediatric patients with IBD. This mixed-methods study included qualitative interviews of pediatric patients and caregivers with demographic/medical variables obtained from medical records. Participants (n = 8) had an average age of 15.62 years (standard deviation = 2.97). Mean length of diagnosis was 4.5 years (standard deviation = 3.6 years). Interviews were transcribed and coded. Qualitative coding of narratives identified main codes of Ostomy Surgery, Preoperative Concerns, Postoperative Concerns, Education Preferences, and Social Concerns, with various subcodes. Codes captured unfamiliarity with the ostomies, preferences for education from a medical provider, and psychosocial concerns. Results suggest pediatric patients with IBD have limited understanding of ostomies and limited insight into educational preferences. These findings highlight the importance of developmentally appropriate information for accessible ostomy education. Abstract : Supplemental Digital Content is available in the text